Agronomic biofortification of fodder sorghum with zinc under different levels of nitrogen - Ahmad, Waqas; Muhammad Tahir,; Ahmad, Riaz; Ahmad, Rashid (Penerbit Universiti Kebangsaan Malaysia, 2018)
Zinc (Zn) deficient soil prevails throughout the world and it has become the bottleneck in achieving production potential and quality of crops. The negligible use of micronutrients along with irregular use of macronutrients is practised for fodder production in Pakistan. Varying levels of zinc (0, 5, 10 and 15 kg ha-1) and nitrogen (0, 60, 120 and 180 kg ha-1) were evaluated for their effect on yield, quality and zinc uptake on fodder sorghum (variety Hegari) in a field experiment for two consecutive years (2014 and 2015). Data were analysed by using Fishers’ analysis of variance (at p<0.05) and response surface methodology (RSM). Correlation between different parameters was also studied. Application of zinc and nitrogen improved the plant height, leaf area plant-1, green fodder yield, dry matter yield, crude protein percentage and zinc content of plant but decreased the neutral detergent fiber, acid detergent fiber and ash percentage. Values for different parameters recorded at second and third levels of zinc and nitrogen were remained at par with each other. Application of 10 kg ha-1 zinc and 120 kg ha-1 nitrogen showed an average increase of 7.3 and 18.6% in green fodder yield while 12.1 and 15.8% in dry matter yield, respectively. Similarly 6.1 and 7.5% increase in crude protein was noted over control. Correlation between NDF and ADF was negative with rest of the studied parameters. In conclusion, Zn2 and N2 gave the best results in term of yield and quality of fodder sorghum.